Reading and editing the Pleurodeles waltl genome reveals novel features of tetrapod regeneration. Issue 1 (December 2017) - Elewa, Ahmed; Wang, Heng; Talavera-López, Carlos; Joven, Alberto; Brito, Gonçalo; Kumar, Anoop; Hameed, L. Shahul; Penrad-Mobayed, May; Yao, Zeyu; Zamani, Neda; Abbas, Yamen; Abdullayev, Ilgar; et al.
Abstract Salamanders exhibit an extraordinary ability among vertebrates to regenerate complex body parts. However, scarce genomic resources have limited our understanding of regeneration in adult salamanders. Here, we present the 20 Gb genome and transcriptome of the Iberian ribbed newtPleurodeles waltl, a tractable species suitable for laboratory research. We find that embryonic stem cell-specific miRNAs mir-93b and mir-427/430/302, as well as Harbinger DNA transposons carrying theMyb -like proto-oncogene have expanded dramatically in thePleurodeles waltl genome and are co-expressed during limb regeneration. Moreover, we find that a family of salamander methyltransferases is expressed specifically in adult appendages. Using CRISPR/Cas9 technology to perturb transcription factors, we demonstrate that, unlike the axolotl, Pax3 is present and necessary for development and that contrary to mammals, muscle regeneration is normal without functionalPax7 gene. Our data provide a foundation for comparative genomic studies that generate models for the uneven distribution of regenerative capacities among vertebrates. The Iberian ribbed newtPleurodeles waltl has a wide spectrum of regeneration abilities. Here, Elewaet al . sequence its 20 Gb genome and transcriptome to investigate the molecular features underlying its regenerative capacities.